2021
DOI: 10.1002/nop2.912
|View full text |Cite
|
Sign up to set email alerts
|

How do nurses and physicians assess inter‐professional collaboration in long‐term care homes? A survey study

Abstract: Good collaboration in healthcare is essential in order to achieve the common goal of safe and high-quality patient care (Reeves et al., 2017). It requires the active contributions of the involved health professionals (Schot et al., 2020). Collaboration in healthcare includes, on the one hand, that different medical professions assume complementary roles and work together in order to address the needs of the patient (O' Daniel & Rosenstein, 2008), but it also means integrating different perspectives, respecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
4
0
3
Order By: Relevance
“…In other countries, for example in Germany, nursing homes mainly employ nursing staff/assistants. The nurses could consult the physician, but there is no frequent or daily collaboration with a general physician [ 44 ]. In that case, professionals from other professions are available remotely from other organisations [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other countries, for example in Germany, nursing homes mainly employ nursing staff/assistants. The nurses could consult the physician, but there is no frequent or daily collaboration with a general physician [ 44 ]. In that case, professionals from other professions are available remotely from other organisations [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in JASSIC scores might reflect the influence of experiences in training courses and clinical practice 23 . Although some reports have compared IPC between two professions, 18,19 few have compared IPC among multiple professions. The comparison in this study revealed higher scores for physicians and social workers.…”
Section: Discussionmentioning
confidence: 99%
“…Zu den zeitnah umzusetzenden Handlungsempfehlungen gehören die berufsgruppenübergreifende Kommunikation, Kooperation und Beratung, die zu einer verbesserten Patientensicherheit führen [ 47 ] und eine Reduktion der Hospitalisierungen aus dem Pflegeheim erwarten lassen [ 27 , 32 , 34 ]. Eine erste Inventarisierung von Kooperationen zwischen Ärzteschaft und Pflegefachpersonal in Deutschland lieferte mögliche Ansatzpunkte für Verbesserungen [ 29 ]. Diese wurden in dem Projekt „CoCARE“ mittels regelmäßiger ärztlicher Visiten, einer gemeinsamen Patientenakte und Medikamentenkontrollen adressiert [ 30 ].…”
Section: Diskussionunclassified